(х²-9)-4(х²-9)+3=0 решите уравнение ​

Nigdui Nigdui    2   18.04.2021 21:03    0

Ответы
vlada3108 vlada3108  18.04.2021 22:00

Объяснение:

( {x}^{2} - 9) - 4( {x}^{2} - 9) + 3 = 0 \\ {x}^{2} - 9 - 4 {x}^{2} + 36 + 3 = 0 \\ - 3 {x}^{2} + 30 = 0 \\ - 3 {x}^{2} = - 30 \\ {x}^{2} = 10 \\ x = \sqrt{10} \: \: \: \: \: \: \: \: x = - \sqrt{10}

ПОКАЗАТЬ ОТВЕТЫ
Фея1011 Фея1011  18.04.2021 22:00

Если условие записано верно, то вот решение


(х²-9)-4(х²-9)+3=0 решите уравнение ​
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра